Exploring Innovative Solutions for Quality of Life and Care of Bed-Ridden Nursing Home Residents through Codesign Sessions - J. van Hoof; M. H. Wetzels; A. M. C. Dooremalen; R. A. Overdiep; M. E. Nieboer; A. M. E. Eyck; P. J. L. M. van Gorkom; E. L. M. Zwerts-Verhelst; S. Aarts; C. Vissers-Luijcks; C. S. van der Voort; M. J. G. A. Moonen; et al. (Journal of Aging Research)
Bed-ridden nursing home residents are in need of environments which are homelike and facilitate the provision of care. Design guidance for this group of older people is limited. This study concerned the exploration and generation of innovative environmental enrichment scenarios for bed-ridden residents. This exploration was conducted through a combination of participatory action research with user-centred design involving 56 professional stakeholders in interactive work sessions. This study identified numerous design solutions, both concepts and products that are available on the marketplace and that on a higher level relate to improvements in resident autonomy and the supply of technological items and architectural features. The methodology chosen can be used to explore the creative potential of stakeholders from the domain of healthcare in product innovation.